DETERMINAN PEMEKARAN WILAYAH DAN FRAGMENTASI PEMERINTAHAN DI INDONESIA - Aan Zulyanto (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2022)
The phenomenon of making new autonomous local government is increasingly widespread in line with the policies of regional autonomy and fiscal decentralization in Indonesia. Many literatures show the local government proliferation in Indonesia is one of the fastest and largest in the world. This study aims to examine the determinants of local government proliferation and government fragmentation in Indonesia. Using panel data from 32 provinces in Indonesia for the period 2001-2013 with fixed effect model (FEM) analysis techniques. The study found that population density, per capita income level, and political aspects are factors that significantly affect territorial splits and government fragmentation in Indonesia. Meanwhile, fiscal capacity, ethnic diversity and income inequality have not been shown to significantly affect the level of fragmentation. The impetus for territorial splits is seen to increase in areas with low population density, high per capita GRDP levels, and high percentage of votes for political parties winning legislative elections. The level of Government Fragmentation in Indonesia is also higher after the implementation of the direct election system for local government head.